2018
DOI: 10.1016/j.adolescence.2018.02.003
|View full text |Cite
|
Sign up to set email alerts
|

The effect of parental style on bullying and cyber bullying behaviors and the mediating role of peer attachment relationships: A longitudinal study

Abstract: The purpose of the present study was the examination of the longitudinal effect of parental style on short-term changes in conventional and cyber forms of bullying/victimization, and the investigation of the mediating role of peer attachment relationships on this effect. The participants were 861 children and adolescents (52% girls, M = 11.72 years) attending Cyprus public institutions. Students provided information during three measurement points. There was a six and a 12 week interval among the three measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
69
1
15

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(96 citation statements)
references
References 91 publications
1
69
1
15
Order By: Relevance
“…Garaigordobil and Machimbarrena (2017) discovered that cybervictims had parents with higher parental stress, who used more permissive educational styles, whereas cyberaggressors had parents with lower levels of parental competence. Charalampous et al (2018) indicated that parental style seemed to affect early adolescents' involvement in cyberbullying and victimization through their influence on peer attachment relationships. More specifically, Govender and Young (2018) noted that authoritarian parenting was significantly and moderately correlated with cyberbullying perpetration.…”
Section: Parental Educational Stylesmentioning
confidence: 99%
See 2 more Smart Citations
“…Garaigordobil and Machimbarrena (2017) discovered that cybervictims had parents with higher parental stress, who used more permissive educational styles, whereas cyberaggressors had parents with lower levels of parental competence. Charalampous et al (2018) indicated that parental style seemed to affect early adolescents' involvement in cyberbullying and victimization through their influence on peer attachment relationships. More specifically, Govender and Young (2018) noted that authoritarian parenting was significantly and moderately correlated with cyberbullying perpetration.…”
Section: Parental Educational Stylesmentioning
confidence: 99%
“…The works studied analyzing the influence of parental educational styles on cyberbullying perpetration and victimization (Charalampous et al 2018;Garaigordobil and Machimbarrena 2017;Govender and Young 2018;Shams et al 2017;Vale et al 2018;Zurcher et al 2018) focused mainly on authoritarian and permissive styles. On the one hand, Govender and Young (2018), Shams et al (2017), andZurcher et al (2018) agree that the authoritarian educational style has a positive relationship with cyberbullying perpetration.…”
Section: Parental Educational Stylesmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, and because of the concept's importance, several studies have been designed to more clearly understand the mechanisms involved in bullying activity and to identify its parameters (Hymel & Swearer, ). Some of the parameters identified so far are interpersonal, such as parental styles and cultural values in the family of origin (Charalambous et al, ; Georgiou, Fousiani, Michaelides, & Stavrinides, ; Georgiou, Ioannou, & Stavrinides, , ), while others are intrapersonal and have to do with individual characteristics such as impulsivity, mindfulness, and moral disengagement (Neumann, Barker, Koot, & Maughan, ; Borders, Earleywine, & Jajodia, ; Fix & Fix, ; Hoaken, Shaughnessy, & Pihl, ; Thornberg & Jungert, ).…”
mentioning
confidence: 99%
“…Keluarga merupakan faktor yang penting bagi bullying, faktor keluarga yang mempengaruhi bullying diantaranya rendahnya fungsi keluarga (Mazzone & Camodeca, 2019) dan pola asuh (Charalampous, Demetriou, Tricha, Ioannou, Georgiou, Nikiforou, & Stavrinides, 2018). Pola asuh yang berpengaruh positif pada perilaku bullying adalah pola asuh otiriter (Bostari & Karagianni, 2014), hal tersebut karena pola asuh otoriter ditunjukan dengan orangtua yang melakukan penghukuman, bentuk hukuman yang diberikan merupakan bentuk kekerasan fisik dan psikologis, melakukan kekerasan untuk menyelesaikan konflik sehingga anak mempresepsikan bahwa orangtuanya tidak sensitif terhadap perasaannya.…”
Section: Keluargaunclassified